Improved HIV and substance abuse treatment outcomes for released HIV-infected prisoners: the impact of buprenorphine treatment. - Springer, Sandra Ann; Chen, Shu; Altice, Frederick L (Journal of urban health : bulletin of the New York Academy of Medicine, 2010)
HIV-infected prisoners fare poorly after release. Though rarely available, opioid agonist therapy (OAT) may be one way to improve HIV and substance abuse treatment outcomes after release. Of the 69 HIV-infected prisoners enrolled in a randomized controlled trial of directly administered antiretroviral therapy, 48 (70%) met DSM-IV criteria for opioid dependence. Of these, 30 (62.5%) selected OAT, either as methadone (N = 7, 14.5%) or buprenorphine/naloxone (BPN/NLX; N = 23, 48.0%). Twelve-week HIV and substance abuse treatment outcomes are reported as a sub-study for those selecting BPN/NLX. Retention was high: 21 (91%) completed BPN/NLX induction and 17 (74%) remained on BPN/NLX after 12 weeks. Compared with baseline, the proportion with a non-detectable viral load (61% vs 63% log(10) copies/mL) and mean CD4 count (367 vs 344 cells/mL) was unchanged at 12 weeks. Opiate-negative urine testing remained 83% for the 21 who completed induction. Using means from 10-point Likert scales, opioid craving was reduced from 6.0 to 1.8 within 3 days of BPN/NLX induction and satisfaction remained high at 9.5 throughout the 12 weeks. Adverse events were few and mild. BPN/NLX therapy was acceptable, safe and effective for both HIV and opioid treatment outcomes among released HIV-infected prisoners. Future randomized controlled trials are needed to affirm its benefit in this highly vulnerable population.
Keywords: Anti-Retroviral Agents; Buprenorphine; CD4 Lymphocyte Count; Female; HIV Infections; Humans; Male; Mental Disorders; Methadone; Middle Aged; Naloxone; Narcotic Antagonists; Narcotics; Prisoners; Substance-Related Disorders